2019
DOI: 10.1186/s12864-019-6034-1
|View full text |Cite|
|
Sign up to set email alerts
|

De novo profiling of RNA viruses in Anopheles malaria vector mosquitoes from forest ecological zones in Senegal and Cambodia

Abstract: Background Mosquitoes are colonized by a large but mostly uncharacterized natural virome of RNA viruses, and the composition and distribution of the natural RNA virome may influence the biology and immunity of Anopheles malaria vector populations. Results Anopheles mosquitoes were sampled in malaria endemic forest village sites in Senegal and Cambodia, including Anopheles funestus, Anopheles gambiae gr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 66 publications
3
13
0
Order By: Relevance
“…In agreement with previous virome studies, most of the taxa derived from honey-baited FTA cards have been identified in various invertebrates [39] and associated to mosquitoes [40]. Additionally, mosquito-specific viruses detected in FTA cards (Table 2) have been described as part of the viral communities harbored by several mosquito species in different geographic regions [41][42][43][44][45][46][47][48]. Bold type corresponds to the selected viruses for primers design.…”
Section: Virome Composition On Honey-baited Fta Cards During Entomolosupporting
confidence: 86%
“…In agreement with previous virome studies, most of the taxa derived from honey-baited FTA cards have been identified in various invertebrates [39] and associated to mosquitoes [40]. Additionally, mosquito-specific viruses detected in FTA cards (Table 2) have been described as part of the viral communities harbored by several mosquito species in different geographic regions [41][42][43][44][45][46][47][48]. Bold type corresponds to the selected viruses for primers design.…”
Section: Virome Composition On Honey-baited Fta Cards During Entomolosupporting
confidence: 86%
“…Similar viRNAs distributions were observed in other insects, such as in whiteflies [24], thrips [29] and bumblebees [27]. It is possible that the 21nt peak we seen in brachycera species such as flies and mosquitoes is unusual for insects [51][52].…”
Section: Discussionsupporting
confidence: 82%
“…2) Cluster content, number and genomic distribution is diverged in both genera [( George et al, 2015 ; Crava et al, 2020 ; Palatini et al, 2020 ). 3) A strong activity of PIWIs and piRNAs in the soma and 4] multiple distinct roles in gene expression are evident in both genera ( Belda et al, 2019 ; Halbach et al, 2020 ). As such, the piRNA pathway represents an enigmatic biological system in mosquitoes, warranting a more aggressive study of the system in mosquito species.…”
Section: Introductionmentioning
confidence: 99%